Exploring the Impact of Artificial Intelligence (AI) on Higher Education for Evolution the Learning (Sebha University Conference Proceedings, 2025)
The potential of artificial intelligence (AI) to enhance teaching and learning procedures is one of its most significant effects on higher education.  By using AI-powered systems, huge amounts of data can be analyzed. To help deliver tailored analytics, tailored recommendations, and tailored student material.   The enhances learning objectives while also fostering a productive and successful teaching environment. This paper explains how different facets of artificial intelligence (AI) affect students' academic performance in higher education. It explores how artificial intelligence (AI) is being incorporated into administrative tasks, student support programs, and instructional methodologies to transform education as a whole. The paper examines how artificial intelligence (AI) may affect learning outcomes, skill development, and student engagement. It places a strong emphasis on the value of adaptable learning environments and techniques for ongoing feedback. In addition to highlighting the many advantages and disadvantages that artificial intelligence (AI) presents for higher education, as shown in this paper, Consequently, the paper offers suggestions for how these technologies might be used by these establishments to promote innovation. So, we can im-prove student outcomes and get them ready for the demands of the workforce of the future.